(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
After the drop of the Indus Valley Civilization, another glorious civilization flourished in India. The individuals who have been to blame for the evolution of the civilization named themselves Aryarns or Aryas. Arya’ literally means the male of’ noble character’, the free born so. They belonged to the number of people referred to as Indo-Europeans. They entered into India from the North West.